PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA - Nurul Jihan Tribuana; Usman; Tahir Maloko (Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem in this research is How to Handle Divorce Due to Domestic Violence in the Barru Religious Court Class II. From the main problem, sub-problems were formulated, namely: 1) What are the Causes of Domestic Violence in Barru Regency, 2) How is the Process for Resolving Divorce Due to Domestic Violence in the Barru Religious Court Class II. The type of research used in this thesis is a qualitative field research (Descriptive Qualitative Research Field). The results of this study indicate that the causes of divorce due to domestic violence in Barru Regency include the husband's temperament or emotional ease, infidelity, matchmaking, influences from outside the home such as drunkenness, and gambling. And the process of resolving divorce cases due to domestic violence at the Religious Courts of Barru Regency is the same as the process of resolving other divorce cases, only slight differences, if domestic violence is in the form of a psychic then added evidence in the form of a doctor's note while domestic violence is in physical form, the proof is not only in written form. however, with witnesses and victim statements, the trial process must use the trial agenda. should have full awareness so that they no longer commit acts of domestic violence, especially to men (husbands), to appreciate and love women (wives) more and resolve disputes, especially divorce due to domestic violence, requires good communication between husband and wife. , in order to create a harmonious and harmonious household. Keywords: Divorce, Domestic Violence.